The fraud audit : responding to the risk of fraud in core business systems - Vona, Leonard W., 1955-; Wiley eBooks (Hoboken, N.J. : Wiley, 2011)
"Essential guidance for creation of an effective fraud audit program in core business systems. The Association of Certified Fraud Examiners has reported that U.S. businesses lose up to $4 billion annually due to fraud and abuse. Discover fraud within your business before yours becomes another business fraud statistic. Fraud in the Core Business Systems provides a proven fraud methodology that allows auditors to discover fraud versus investigating it. Explains how to create a fraud audit program. Shows auditors how to locate fraud through the use of data mining. Focuses on a proven methodology that has actually detected fraudulent transactions. Take a look inside for essential guidance for fraud discovery within specific corporate F & A functions, such as disbursement, procurement, payroll, revenue misstatement, inventory, journal entries, and management override."--
Front Matter -- What Is a Fraud Audit? -- Professional Standards -- Fraud Scenarios -- Brainstorming: The Implementation of Professional Standards -- Assessment of Fraud Likelihood -- Building the Fraud Audit Program -- Data Mining for Fraud -- Fraud Audit Procedures -- Document Analysis -- Disbursement Fraud -- Procurement Fraud -- Payroll Fraud -- Revenue Misstatement -- Inventory Fraud -- Journal Entry Fraud -- Program Management Fraud -- Quantifying Fraud -- Appendix A: Fraud Audit Program: Payroll -- Appendix B: Fraud Audit Program: Disbursements -- Appendix C: Fraud Audit Program: Procurement -- Appendix D: Fraud Audit Program: Inventory -- Appendix E: Fraud Audit Planning Program: Revenue Recognition -- Appendix F: Checklist of Inherent Scheme Structure -- Appendix G: Fraud Audit Matrix -- About the Author -- Index.
John Wiley and Sons
Keywords: Fraud investigation -- United States; Forensic accounting -- United States; Fraud -- United States -- Prevention; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; BUSINESS & ECONOMICS -- Workplace Culture; Forensic accounting; Fraud investigation; Fraud -- Prevention; United States; Electronic books